Implementation Of Loose Parts-Based Learning To Enhance Student Engagement In Islamic Religious Education For Children Aged 5-6 Years - Zakiyah Zakiyah; Nikem Kurnia Ningsih; Ujang Sugara; Purwanto Purwanto; Hany Arianti (Jurnal Pendidikan Anak, 2026)
This study aims to describe the implementation of loose parts-based learning in Islamic Religious Education (IRE) at school and to analyze improvements in student engagement in IRE learning following its application. Student engagement was examined through three dimensions: cognitive, affective, and psychomotor. The study employed a classroom action research design. The research subjects were children aged 5–6 years. Data were collected through observations, reflections, and learning documentation. The results indicate that in the initial condition, student engagement was relatively low due to the dominance of conventional teaching methods. The implementation of loose parts-based learning in Cycle I enhanced student engagement, though challenges related to learning focus and classroom management remained. Improvements made in Cycle II, through more structured activities and more effective classroom management, resulted in a significant and stable increase in student engagement across all dimensions. Students demonstrated better understanding, higher learning enthusiasm, and more active physical and social participation. These findings contribute to the Development of innovative pedagogical practices by demonstrating that loose parts constitute a practical approach to enhancing learning engagement and supporting meaningful learning in character and religious education.